ANALISIS KAJIAN SOSIAL EKONOMI PEMBANGUNAN DAN PERLUASAN TOSERBA “ X ” - Desfitriady, Desfitriady; Kusmayadi, Tatang (2018)
The purpose of this study is to know and understand the community in the Village Sayati Margahayu District Bandung regency with the development and extension of department store (Convenience Store) "X". The research method is descriptive method using qualitative and quantitative approach as the basis of analysis and interpretation. Sample determination technique used is cluster with simple random sampling method and purposive sampling, which means that the sample used in accordance with the purpose of research. Data which is primary and secondary data. The results showed that people responded positively and variedly about the decision to the extension of the "X" Stores, and only a small portion would be used, but it was only up to the government.